Peran Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Kalimantan Tengah dalam Menangani Dugaan Pelanggaran Hak Asasi Manusia - Simarmata, Swiss Van; Heriamariaty, Heriamariaty; Noor, Syamhudian (Neolectura, 2025)
Handling Alleged Human Rights Violations is the process of resolving alleged human rights violations that occur in the community, both complained (reported) and uncomplained (unreported), which is one of the duties and functions of the Ministry of Law and Human Rights as a form of the Government's seriousness in implementing the protection and fulfillment of human rights in Indonesia. The Regional Office of the Ministry of Law and Human Rights of Central Kalimantan as an extension of the Ministry of Law and Human Rights in the region is obliged to carry out activities to handle alleged human rights violations, especially in Central Kalimantan Province, and is expected to be a solution in resolving alleged human rights violations experienced by the people of Central Kalimantan. The purpose of this study is to understand and examine the role of the Regional Office of the Ministry of Law and Human Rights of Central Kalimantan in handling alleged human rights violations, analyzing obstacles to handling and resolving alleged human rights violations carried out by the Regional Office of the Ministry of Law and Human Rights of Central Kalimantan. The research method used in this study is empirical legal research, with a sociological approach, namely analyzing the effectiveness of the enforcement of a legal rule in society. Based on the results of the study, it can be taken that the role of the Regional Office of the Ministry of Law and Human Rights of Central Kalimantan in carrying out activities to handle alleged human rights violations, both those communicated directly and indirectly, especially in Central Kalimantan Province, has been carried out quite well in accordance with the main tasks and functions of the Regional Office of the Ministry of Law and Human Rights, although in its implementation there are still several obstacles or obstacles faced by the The team from the Human Rights Sector, both internal and external obstacles. The Regional Office of the Ministry of Law and Human Rights of Central Kalimantan has made efforts to overcome these obstacles by increasing the capacity of officials and employees in the field of human rights, maximizing the existing budget and further improving coordination with the Echelon I Unit of the Ministry of Law and Human Rights and related agencies.